A New Approach to Risk Assessment Model and Management for Jetty Fuel Terminal Industrywide Using Risk Priority Number - Yoseph Valentino Silalahi; Badrul Munir; Yudha Pratesa (Recent in Engineering Science and Technology, 2025)
Jetty is an essential part of a fuel terminal and oil distribution process in terms of loading and unloading oil from and to tanker. Jetty has been widely used in fuel supply point facilities in archipelago countries like Indonesia. The increase in the importance given to maritime transportation has not only resulted in the development of the structure of safety issues but has also led to new investigations into the design of ships, the configuration of ports, and the operations conducted, all of which are essential components. However, it is not possible to ignore the risk inherent in jetty fuel terminal operations. Most of the reseach have pre-dominantly focused on the operation and impact of ship maneuvers and ship operations. But focusing on the jetty fuel risk itself is also very important as a whole part of reliability of a fuel receiving facility. FMEA is frequently used as a risk analysis method in determining risks arising from oil and gas sector. Each category of Severity, Occurance, and Detection from each risk factor can be rated to obtained the Risk Priority Number value. Mooring facilities assessment furthermore provides the implementation of assessment (grading) of operational suitability of jetties, based on the results of a visual assessment and special inspections. This paper aims to identify the risk associated with and to analyze these risk using Risk Priority Number ranking.